O ensino de língua portuguesa como língua de acolhimento a imigrantes: por uma contribuição sociolinguística - Vieira, Leandro Rocha (My University, 2019)
This research has as objective to propose new strategies to the teaching of Portuguese language as host language to foreigners, in an effort to collaborate with the development of linguistics, social and intercultural competence of these individuals, in particular, those who went to the classes of the project Portuguese Language as passport to citizenship in the Bento Gonçalves campus of the Federal Institute of education, science and technology of Rio Grande do Sul (IFRS). Therefore, concepts as language, culture, society and immigration are approached starting by the proposes of Cuche (2002), Bourdieu (1998), Pesavento (2002), Bagno (2002, 2012), Grosso (2010), and Zamberlan et al., (2014). This investigation is built on the theoretical assumption of Sociolinguistics, in particular, the studies of Labov ([1976 2006), Calvet (2002) and Bagno (2002, 2012) and Communicative Competence by the studies of Coseriu (1992) and Hymes (1996, 2006), which we seek to demonstrate the intrinsic relation between those concepts. Based on that, we reflect about how these theories are transposed to education and incorporated to the teaching and learning, being perceptible in the methodological making of the teacher and in the language use by the student, which are in linguistic and cultural immersion in our community. In this way, starting with the classroom practice and text production of the learners, we verify how the pedagogical making happens and how the students are assimilating the language, at the point when emerged some difficulties, and it’s based on this that we propose actions. To the realization of this analysis work of Reference for Languages: Learning, Teaching, Assessment (CEFR), in terms of descriptors and proficiency levels, specifically the levels A1, A2 and B1, with we rated those learners. We conclude with this research that the sociolinguistics assumptions and communicative competence have potential to substantiate theoretically the teaching and learning of portuguese as host language and that these activities can be better developed by language skills associated with social and intercultural issues, consequently providing more significant experiences in the language and effective social integration of the immigrants.
Esta pesquisa tem como objetivo propor novas estratégias de ensino de língua portuguesa como língua de acolhimento (PLA) a imigrantes no sentido de colaborar com o desenvolvimento de competências linguísticas, sociais e interculturais desses sujeitos, em especial, daqueles que frequentam aulas no Projeto Língua Portuguesa como passaporte para a cidadania, no campus Bento Gonçalves do IFRS. Para tanto, são abordados conceitos como língua, cultura, sociedade e imigração a partir do que é proposto por Cuche (2002), Bourdieu (1998), Pesavento (2002), Bagno (2002, 2012), Grosso (2010) e Zamberlan et al. (2014). Esta investigação está pautada nos pressupostos teóricos da Sociolinguística nos estudos de Labov ([1976] 2006), Calvet (2002) e Bagno (2002, 2012) e da Competência Comunicativa, nos ensinamentos de Coseriu (1992) e Hymes (1972, 2006). Procuramos, assim, demonstrar a intrínseca relação desses conceitos. Para tanto, refletimos sobre como essas teorias são transpostas à educação e incorporadas ao ensino e à aprendizagem da língua, sendo perceptíveis no fazer metodológico do professor e na realização da linguagem pelos alunos, que se encontram em situação de imersão linguística e cultural. Assim, a partir da prática de sala de aula e de produções textuais dos estudantes, verificamos como acontece o fazer pedagógico e como os aprendizes vêm assimilando a língua, momento no qual emergiram algumas dificuldades, e é com base nisso que propomos ações. Para a realização da análise, tomamos como parâmetro o que é proposto pelo Quadro Europeu Comum de Referência para as Línguas (QECR), em termos de descritores e níveis de proficiência, especificamente, no que se refere aos níveis A1, A2 e B1, nos quais classificamos esses indivíduos. Concluiu-se com esta pesquisa que os pressupostos da sociolinguística e da competência comunicativa têm potencial para fundamentar teoricamente o ensino e a aprendizagem de PLA, e que essas atividades podem ser melhor desenvolvidas com conhecimentos linguísticos associados a questões sociais e interculturais, proporcionando-se, assim, experiências mais significativas na língua e na efetiva integração social dos imigrantes.
Keywords: Língua portuguesa - Estudo e ensino; Língua portuguesa - Métodos de ensino; Aquisição da segunda língua - Aspectos culturais; Imigrantes; Portuguese Language - Study and Teaching; Portuguese Language - Teaching Methods; Second Language Acquisition - Cultural Aspects; Immigrants